Estudo sobre Rhyzophora mangle L. I. As células espiculares do hipocótilo - Oliveira, Raul José Millen de (Acta Biológica Paranaense, 1976)
Estudo sobre Rhyzophora mangle L. I. As células espiculares do hipocótilo